Digital Governance in the Unhabilitable House Program (Opportunities and Challenges) in Majalengka District - Febrianti Hardian, Eri; Ilhami, Rizky (Journal of Management, 2024)
The Majalengka Regency government is trying to innovate in the uninhabitable house program (RUTILAHU) through the Housing, Settlement Areas and Lands Office. However, digital-based community services are still not optimal. Many data on related websites such as jdih.majalengkakab.go.id and dpkpp.majalengkakab.go.id have not been transparent and often experience errors, such as information about the budget, number, and achievement targets of the RUTILAHU program that have not been updated. In addition, there is a discrepancy between online data about the RUTILAHU program and the original data in the relevant agencies. The research method used is a qualitative method. The results and research in the management of the RUTILAHU program data collection on e-RTLH are considered not good because there are still frequent changes to e-RTLH so that the site often experiences errors. In addition, e-RTLH is also not optimal in terms of data transparency to the community. On the dpkpp.majalengkakab.go.id website, not all data has been processed and uploaded to e-RTLH.